Humanitarian Law Education for Military Members in Preventing Violations and Building Combat Professionalism - Saiful Alam; Rooy Candra Sihombing; Tarsisius Susilo; Benny Limbong; Agus Soeprianto (International Journal Labs, 2025)
Humanitarian law education for military members is a fundamental pillar in efforts to build the professionalism of soldiers while preventing human rights violations during armed conflict. This study analyzes the urgency and effectiveness of humanitarian law education in the military environment, highlighting educational approaches, implementation challenges, and real impacts on the field. Departing from the assumption that a lack of understanding of humanitarian law is one of the root causes of violations that occur in war, this study presents a critical examination of training programs in several countries that have successfully implemented them systematically, such as Switzerland, Norway, and Colombia. Using a qualitative approach and literature study methods, this article constructs the argument that humanitarian law education not only instills legal norms, but also shapes the moral integrity and combat ethics of a soldier. The results of the study show that a structured, realistic, and contextual humanitarian law education program is able to significantly reduce the potential for violations. In Indonesia, humanitarian law education still faces structural and cultural challenges, such as a lack of integration in the basic military curriculum and a limited number of competent instructors. Therefore, this article recommends a comprehensive reform of the military curriculum, teacher capacity building, and strengthening post-training evaluations. Overall, this article emphasizes that humanitarian law education is an indispensable prerequisite for creating a professional, humanistic, and international standard military force. Through the formation of a strong understanding of the law since basic education, it is hoped that soldiers will be able to balance the success of combat missions with adherence to universal humanitarian values.